Akhlak Guru dan Murid Menurut Ibnu Jama’ah dan KH Hasyim Asy’ari - Ahmad Fairuz; Abuddin Nata; Khalimi Khalimi (Jurnal Syntax Admiration, 2024)
The occurrence of various social problems lately, especially in the field of education, especially moral issues in the world of education has become a problem in itself. This requires separate research to overcome these problems. This study aims to analyze the morals of teachers and students according to Ibn Jama'ah and KH. Hasyim Asy'ari, and comparing the thoughts of the two and then afterwards relevant to teacher competence that is common in Indonesian education today. The type of research used in this study is qualitative and the methods used include literature research methods, which produce data in the form of written words from analyzed data sources. This research also uses content analysis techniques in data processing. The primary data sources used are Kitab Tadzkiratu as-Sami wa al-Mutakallim by Ibn Jama'ah and Kitab adabu al-'Alim wa al-Muta'allim by KH. Hashim Ash'ari. While the secondary data sources are books or other references related to the moral statements of teachers and students. The similarity with the conclusions of other academics is the research method used, namely qualitative research methods. While the difference is in the results of the research, which may be due to differences in the material presented and the time of research. In conclusion, there are similarities between the moral concepts of teachers and students according to Ibn Jama'ah and KH. Hashim Ash'ari. While the difference between the thoughts of the two lies in the difference in diction and the existence of discussions that are only discussed in one of each of the books of both.